Relatório do estágio curricular supervisionado em Medicina Veterinária – área: clínica médica de pequenos animais - Gonçalves, Fernanda Moreira (2019)
This report describes the activities carried out and / or accompanied by the student Fernanda Moreira Gonçalves, during the Supervised Curricular Internship in Veterinary Medicine (ECSMV), in the area of small animal medical clinic. The internship took place from January 7 to March 29, 2019, making up the total of 456 hours, with the guidance of Professor Dr. Marília Teresa de Oliveira. THE choice of the internship location, the University Veterinary Hospital of the Federal de Santa Maria (HVU-UFSM), located in Santa Maria-RS, took place in virtue of the local casuistry and the fact that it is a reference teaching hospital in the area pet clinic in the region. The internship was supervised by professor Dr. Saulo Tadeu Lemos Pinto Filho. 165 diagnoses were established in total, 119 in canine patients, and 46 in felines. Of these, two clinical cases for reporting and discussion: Multicentric lymphoma in a feline and botropic accident in a canine. Finally, it was concluded that the curricular internship had achieved, since the case series with numerous diseases and the monitoring of different professionals, with different clinical procedures, provided the development of the critical vision, contributing to the formation of the conduct that will be adopted after academic training.